Estimation of the Value at Risk Using the Stochastic Approach of Taylor Formula - Vini Yves Bernadin Loyara; Remi Guillaume Bagré; Diakarya Barro (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to provide an approximation of the value-at-risk of the multivariate copula associated with financial loss and profit function. A higher dimensional extension of the Taylor–Young formula is used for this estimation in a Euclidean space. Moreover, a time-varying and conditional copula is used for the modeling of the VaR.